Barrett esophagus in routine diagnosis - A histopathological approach related to practice Barrett-ösophagus im alltag - Ein praxis-bezogener zugang zur histopathologischen diagnostik - Zonnur, S.; Vieth, M. (Verdauungskrankheiten, 2010)
While most clinicians and pathologists would agree that Barrett esophagus is a precancerous condition, a standardized definition of Barrett esophagus does not exist. Worldwide pathologists use different definitions of Barrett esophagus, not all of them including goblet cells. There are models of Barrett's esophagus as the result of a multistep process, in which the occurrence of goblet cells might be a secondary event. Recent studies show that even Barrett carcinoma can develop in areas without goblet cells. The high interobserver variation complicates the diagnosis of neoplasia. New endoscopic resection techniques can be used for therapy with curative intent and allow for an alternative to surgery. In the pathologist's report should be included all data the clinician needs for planning the further therapy. © 2010 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett carcinoma; Barrett esophagus; Columnar metaplasia; Endoscopic ablation; Endoscopic resection specimen; Esophageal adenocarcinoma; Intraepithelial neoplasia